2006
DOI: 10.1007/s10126-006-6014-8
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Analysis of Japanese Sea Cucumber, Stichopus (Apostichopus) japonicus, Supports Reproductive Isolation in Color Variants

Abstract: The genetic relationship among the three color variants (Red, Green, and Black) of the Japanese sea cucumber, S. japonicus, was investigated using 11 microsatellite markers. Genetic differentiation testing among the three sympatric color types showed the strong heterogeneity of Red (p<0.001), while no significant difference was observed between Green and Black (p=0.301 to 0.961). UPGMA trees constructed from 10 sample lots from 5 localities showed two distinct clusters, one from the Red types and the other fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 26 publications
6
40
0
Order By: Relevance
“…1). The genetic relationship between black and green types in Apostichopus japonicus was examined using 11 microsatellite markers and it was concluded that sympatric black and green types belonged to the same population (Kanno et al, 2006). The surface water temperature was 7.4 C and the salinity of surface water was 2.85% at the sampling point.…”
Section: Methodsmentioning
confidence: 99%
“…1). The genetic relationship between black and green types in Apostichopus japonicus was examined using 11 microsatellite markers and it was concluded that sympatric black and green types belonged to the same population (Kanno et al, 2006). The surface water temperature was 7.4 C and the salinity of surface water was 2.85% at the sampling point.…”
Section: Methodsmentioning
confidence: 99%
“…However, information concerning the red race of sea cucumber is limited and mainly focuses on the evaluation of the color variation and genetic differentiation among the three color variants (Kanno and Kijima 2001Kanno et al 2006). There are few reports about the hatchery production of the red race of A. japonicus.…”
Section: Introductionmentioning
confidence: 98%
“…Kanno and Kijima (2002) found the red color is discontinuous from the other color races quantitatively (numerical value of the skin color by L*a*b color model) and qualitatively (pigment composition), while the green and black variants show continuous color distribution and the same pigment composition. Microsatellite analysis of the three color variants indicates a separate species status for the red variant and the other color races (Kanno et al 2006). Color variation is one of this species' most important traits, affecting the price and taste of the products.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that sea cucumber can be divided into green, red and black morphs (Kanno et al 2006, Kang et al 2011. White sea cucumber, a genetic albino variant, is rare in nature (Ma et al 2014a) and extensively believed to be rich in the element selenium, and consequently has a high market value.…”
Section: Introductionmentioning
confidence: 99%